Infertile Couple Pursuing for a Desired Child- a clinical case study - Mônica OB Oriá; Lorena Barbosa Ximenes (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
In the Northeast Brazil the pregnancy is culturally related to femininity (woman) and virility (man) therefore to be infertile can threaten the marriage union. To describe the infertile couple's experience who lives in Northeast Brazil and was submitted to in vitro fertilization (IVF), we conducted a clinical case study with qualitative approach using the Symbolic Interactionism (Blumer, 1969) and Thematic Analysis (Bardin, 1979) as theoretical and methodological framework, respectively. This study revealed that to submit to IVF is an experience full of conflict and uncertainty, requiring an especialized assistance in regards to human reproduction and a holistic nursing care considering the cultural issues.